2020
DOI: 10.3855/jidc.13003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, frailty and long-term care: Implications for policy and practice

Abstract: Older adults have been disproportionately affected by the COVID-19 pandemic, with many outbreaks occurring in Long Term Care Facilities (LTCFs). We discuss this vulnerability among LTCF residents using an ecological framework, on levels spanning from the individual to families and caregivers, institutions, health services and systems, communities, and contextual government policies. Challenges abound for fully understanding the burden of COVID-19 in LTCF, including differences in nomenclature, data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 23 publications
(26 reference statements)
0
49
0
Order By: Relevance
“…Some reports argued that frail individuals may develop more severe COVID-19 disease [ 3 , 4 ]. However, data is inconsistent as it has also been suggested that there may be a sort of resilience by which certain frail subjects remain asymptomatic [ 5 ]. To our knowledge, there are no studies addressing if frail subjects are more prone to acquire SARS-CoV-2 infection in endemic communities, independently of risk factors inherent to aging or other comorbidities.…”
Section: Clinical/scientific Notementioning
confidence: 99%
“…Some reports argued that frail individuals may develop more severe COVID-19 disease [ 3 , 4 ]. However, data is inconsistent as it has also been suggested that there may be a sort of resilience by which certain frail subjects remain asymptomatic [ 5 ]. To our knowledge, there are no studies addressing if frail subjects are more prone to acquire SARS-CoV-2 infection in endemic communities, independently of risk factors inherent to aging or other comorbidities.…”
Section: Clinical/scientific Notementioning
confidence: 99%
“…Additionally, worldwide reports have confirmed the high risk of severe illness from COVID-19, including the need for hospitalization, intensive care and death, in older adults, particularly in those with comorbidities (e.g., cardiovascular and respiratory diseases, morbid obesity, diabetes, chronic kidney disease, cancer, gastrointestinal, skin, muscleskeletal, and immune diseases) [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Disease spread increases when staff are required to re-use personal protective equipment because of shortages, when staff work at more than one facility; and when training level is low. Andrew et al, (2020) point to the socio-environmental policy level, in order to understand system-level problems. These include COVID-19 testing ability, availability of personal protective equipment, resident and congregate room size, staff training in infectious disease, and synchronized administrative organization for mitigation strategies, all of which can be highly variable across health care jurisdictions and facilities [147].…”
Section: Absorbmentioning
confidence: 99%
“…Andrew et al, (2020) point to the socio-environmental policy level, in order to understand system-level problems. These include COVID-19 testing ability, availability of personal protective equipment, resident and congregate room size, staff training in infectious disease, and synchronized administrative organization for mitigation strategies, all of which can be highly variable across health care jurisdictions and facilities [147]. There is also potential for applying or adapting communication technology that can be used by residents to stay connected with family and friends.…”
Section: Absorbmentioning
confidence: 99%